Using a Systems Thinking Approach for a Dynamic Hydrogen Risk Assessment - Julio Ariel Dueñas Santana; Ernesto Salzano; Almerinda Di Benedetto; Ruben Van Coile (Chemical Engineering Transactions)
The rising global demand for cleaner energy sources brings an increasing complexity regarding the risk level and safety management of gas fuels. In order to address this complexity, this research adopts a Three-Paradigm integration (considering Sustainability, Complexity, and Systems Thinking) to perform a dynamic hydrogen risk assessment, and proposes an integrated Systems Thinking approach which captures interdependencies linked to the hydrogen risk. In this study, a Causal Loop Diagram is developed to understand the dynamics and the complex behaviour related to hydrogen safety. A System Dynamics model is proposed for computing the dynamic failure probability and the likelihood of domino effects for pressurized vessels. The development of the System Dynamics models offers valuable insights for policymakers, industry stakeholders, and researchers alike. Overall, the integration of a Systems Thinking approach allows for a better understanding of the complex interactions involved in the risk assessment of hydrogen, allowing for informed decision-making and advancements in gas storage technologies.